The Effect of Flossing Techniques on Gum Health and Caries Prevention - Henny Sutrisman; Calvin Conelly; Rosmerry Simanjuntak; Adrianus Prihartanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Gum health and caries prevention are important aspects in maintaining overall oral health. Flossing technique or the use of dental floss is known as one of the effective methods for cleaning areas between teeth that are not reached by a toothbrush. This study aims to analyze the effect of flossing technique on gum health and caries prevention. This study used an experimental method involving 100 respondents who were divided into two groups, namely the group that routinely flossed and the control group that only relied on a toothbrush. Data were collected through gum health examinations using the gingival index and caries detection through clinical examinations for 3 months. The results showed that the group that routinely flossed experienced a significant decrease in the level of gum inflammation compared to the control group. In addition, the flossing technique was also proven effective in reducing plaque formation between teeth, which is the main factor causing caries. In conclusion, the flossing technique has a positive effect on gum health and can play an important role in caries prevention. Therefore, the use of flossing is recommended as part of an oral hygiene routine to support optimal dental and gum health.